Legal Politics of the Recognition of Indigenous Customary Land Rights in West Papua After the Constitutional Court Ruling on Customary Forests - Jandrie Sembiring; Rahayu Subekti; Rosita Candrakirana (Pelopor Publikasi Akademika, 2026)
The recognition of indigenous people’s customary land rights in Indonesia remains a persistent legal and political issue, particularly in regions where customary law continues to function as a living normative order, such as West Papua. A major constitutional development occurred through Constitutional Court Decision No. 35/PUU-X/2012, which affirmed that customary forests are no longer part of state forests, thereby strengthening the legal position of indigenous peoples over their traditional territories. However, this juridical progress has not automatically resulted in effective recognition and protection at the administrative level. This study examined the legal politics underlying the recognition of customary land rights in West Papua in the aftermath of the Constitutional Court’s decision. Using a socio-legal approach combined with doctrinal legal analysis, this paper explores the tension between normative recognition and empirical implementation in land administration practices. The study finds that the post-decision legal framework still reflects a state-centric orientation, in which recognition of indigenous rights remains dependent upon bureaucratic validation, fragmented regulation, and formal governmental determination of indigenous communities. In West Papua, these challenges are intensified by legal pluralism, overlapping regulatory regimes, and the absence of adaptive mechanisms for communal land registration. This paper argues that the existing legal politics has not yet fully moved from symbolic recognition toward substantive justice. Therefore, a reconstruction of legal policy is necessary, integrating legal pluralism, participatory mapping, and institutional recognition of customary authorities within the national land administration system.